La traction animale - Havard , Michel; Vall , Éric; Lhoste , Philippe (éditions Quae, 2010)
Draught animals can reduce the laboriousness of human work and lessen poverty in developing countries by facilitating soil cultivation and transport. This updated and illustrated practical summary of knowledge on animal traction is enriched with results from recent experiments into animal well-being, producer and craftsman associations and environmental impact.